RELASI JENDER DALAM PERSPEKTIF PESANTREN - Iyoh Mastiyah (Jurnal Dialog, 2017)
Some people understand and practice the relationship of men and women are not equal. Men are often perceived as superior to women. Therefore, the relation of men and women continues to be debate among the public, especially in Islamic thought, even as the seriousness of the pesantren kyai makes gender relations as the central discourse. In this regard, this paper will discuss how gender relations in the perspective of Islamic boarding school (pesantren)? KEY WORDS:gender relation, Islamic boarding school, Islamic thought, gender equality.